From myth to allegory: a study of the poetry of W.H. Auden, with special reference to the poet's intention - Bell, I M (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1968)
The more attentively Auden's poetry is studied, the more one critical problem emerges. How can the poet of the "twenties and ' thirties be reconciled with the poet of the last three decades? "We've all got to come to terms with the later Auden" writes Professor Richard Hoggart, but he does not explain how. The man who wrote the pungent early poetry with its constant reiteration of warnings to a sick society that what was needed was " "¦ death, death of the grain, our death, Death of the old gang "¦ " before it could achieve "new styles of architecture, a change of heart", seems an entirely different person from the man who is on the side of Authority to-day; that is to say in so far as Auden can ever be said to be definitely on one side or another. Intro. p. 1.
Keywords: Auden, W. H., (Wystan Hugh), 1907-1973 -- Criticism and interpretation